LEGAL ASPECTS OF THE ACTIVITY OF SOCIAL BUILDING SOCIETIES IN THE IMPLEMENTATION OF HOUSING POLICY - Lalak, Iga (Review of European and Comparative Law, 2018)
Participation in the creation of a social housing association in its proper functioning is a very important part in the implementation of housing policy. In spite of this, the institution of the society is still insufficiently clarified, since determining a flat which in 30% is financed by a citizen as a social one seems to be a vague term. The aim of the publication is to analyze the issue of social housing associations, but first of all to show the advantages and disadvantages of this system and the indeterminate scope of the state’s responsibilities in the area of supporting housing construction.